UPAYA PENCEGAHAN POTENSI TERJADINYA TINDAK PIDANA KORUPSI PADA PROSES PENERIMAAN CALON ANGGOTA POLRI MELALUI WHISTLEBLOWING SYSTEM (Studi Pada Biro Sumber Daya Manusia Polda Sumatera Barat) - Saputra, Eggy (Universitas Ekasakti, 2022)
Professional recruitment of members of the National Police is a must as regulated in Perkap Number 10 of 2016 concerning the Admission of Candidates for Members of the Indonesian National Police. The National Police presents a whistleblowing system application in order to prevent the occurrence of criminal acts that occur in the process of accepting prospective members of the Police. Through the National Police Chief's Decree Number: Kep/274/11/2019 concerning Team Membership Structure and the Use of the Whistleblowing System Application for the Admission of Police Candidates, this is an internal effort made by the National Police in preventing the practice of irregularities both ethically by the Police and acts that are included in Corruption.